Outcome of Radiocephalic Arteriovenous Fistula Constructed Under Brachial Plexus Block Versus Local Anesthesia: A Randomized Controlled Trial (Bangladesh Journal of Urology, 2022)
Backgrounds: Hemodialysis (HD) is the commonest modality of renal replacement therapy (RRT) which needs vascular access. Ideal vascular access should be well functional, durable, stable, and have fewer complications. An arteriovenous fistula (AVF) is the preferred form of vascular access and is recommended by Kidney Disease Improving Global Outcome (KDIGO) guidelines. Most of the AVFs are constructed under local anesthetic infiltration which has a high failure rate which is about 30-40% for radiocephalic arteriovenous fistula (RCAVF). This study aimed to change the anesthetic technique to brachial plexus block (BPB) for RCAVF creation to improve the primary patency rate and reduce early thrombotic complications.Objectives: The objective was to see the effect of brachial plexus block (BPB) on the outcome of AVF creation by primary patency rate, maturation time, primary functional patency rate, and complications.Materials and Method: This was a randomized controlled trial conducted in the Department of Urology, Bangabandhu Sheikh Mujib Medical University, Dhaka from December 2018 to December 2019. A total of 80 patients were selected from the study population according to inclusion and exclusion criteria. Then divided into two groups by simple random sampling. In the group, A RCAVF constructed under BPB, and group B RCAVF was constructed under LA. The standard operation technique of AVF construction was followed. Evaluation of AVFs was done at 3rd POD, 2nd week, 6th week, and 12th weeks to see the functional status and any complications. Doppler US was done at the 6th week routinely.Results: Among these 80 patients 3 patients were lost from the follow-up, two from group A and one from group B. There was no significant difference in age, sex, comorbidities, and HD status between the groups. There was higher primary patency in group A at 3rd POD and 2nd weeks but was not statistically significant. In the 6th week primary patency in group A was 33/38 (86.8%) and in group B 25/39(64.1%), p=0.033. In the 12th week, primary patency and functional primary patency rate were in group A was 33/38 (86.8%) and in group B 25/39(64.1%), p=0.033 and statistically significant. No significant difference in maturation time between the groups. Thrombosis was the most common complication, 14 in group B and 5 in group A. One BPB was failed but there was no significant complication related to BPB.Conclusion: Radiocephalic arteriovenous fistula constructed under brachial plexus block has better primary patency and functional primary patency than local anesthesia at 6th and 12th week. Early thrombotic complications were higher in AVF creation under local anesthetic infiltration. Anaesthesia with BPB can be used for primary radiocephalic AVF construction surgery to improve the outcome of RCAVF fistula and early complications.Bangladesh J. Urol. 2021; 24(2): 129-134